Water soluble fertilizers in horticultural crops— An appraisal - MALHOTRA, S K (The Indian Journal of Agricultural Sciences, 2016)
Horticultural crops have now attained a status, parallel to not only field crops, but stake strong claim of offering nutritional security, thereby, cutting the unnecessary load on consumption of cereals. However, raising productivity of horticultural crops is still a constraint. One of the prime reasons is the abysmal use of fertilizers, hardly 10% of total fertilizer use is diverted towards the share of horticultural crops. Of different fertilizers, liquid fertilizers are again a special class of fertilizers, hold very strong promise in protected cultivation, hydroponic/aeroponic or even open field hydroponic for perennial fruit crops. The liquid fertilizers, as special class of fertilizers provide an enormous possibility of tailoring nutrient use across critical growth stages, a pre-requisite for better nutrient-use-efficiency. Customized fertilization/fertigation is another potential reality, besides its suitability in site specific nutrient managements. In this background, these issues have been addressed in this review.